Lewis's medical-surgical nursing : assessment and management of clinical problems - Lewis, Sharon L.; Dirksen, Shannon Ruff ;Heitkemper, Margaret McLean ;Bucher, Linda ;Camera, Ian M. ;Borromeo, Annabelle (Singapore : Mosby Elsevier, 2014)
Offers up-to-date, evidence-based coverage of the latest clinical developments you need to know to provide exceptional care in today's fast-paced health care environment.
Concepts in nursing practice -- Pathophysiologic mechanisms of disease -- Perioperative care -- Problems related to altered sensory input -- Problems of oxygenation: ventilation -- Problems of oxygenation: transport -- Problems of oxygenation: perfusion -- Problems of ingestion, digestion, absorption, and elimination -- Problems of urinary function -- Problems related to regulatory and reproductive mechanisms -- Problems related to movement and coordination -- Nursing care in specialized settings
Keywords: NURSING